Water, sanitary, and waste services for buildings - Wise, A. F. E. (Longman, 1995)
Water use, load and storage estimation, water installations, principles of soil and waste pipe installations, design of oil and waste pipe installations, environmental considerations ventilation, solid waste storge and handling.